2018
DOI: 10.1186/s12935-018-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of membrane cholesterol compromised caspase-8 imparts in autophagy induction and inhibition of cell migration in cancer cells

Abstract: BackgroundCholesterol in lipid raft plays crucial role on cancer cell survival during metastasis of cancer cells. Cancer cells are reported to enrich cholesterol in lipid raft which make them more susceptible to cell death after cholesterol depletion than normal cells. Methyl-β-cyclodextrin (MβCD), an amphipathic polysaccharide known to deplete the membrane cholesterol, induces cell death selectively in cancer cells. Present work was designed to identify the major form of programmed cell death in membrane chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…The contribution of chol in cell migration/invasion is not new but data are often contradictory. Indeed, chol depletion has been shown to reduce breast cancer cell lines migration [ 53 , 54 ] while its supplementation promotes migration and invasion of renal carcinoma cells [ 55 ]. Conversely, lower membrane chol content correlates with increased invading capacity compared to non-invading cells [ 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of chol in cell migration/invasion is not new but data are often contradictory. Indeed, chol depletion has been shown to reduce breast cancer cell lines migration [ 53 , 54 ] while its supplementation promotes migration and invasion of renal carcinoma cells [ 55 ]. Conversely, lower membrane chol content correlates with increased invading capacity compared to non-invading cells [ 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase‐8 can directly cleave caspase‐3 to activate apoptosis or GSDMD to trigger pyroptosis, as well as also cleaving RIPK1 and RIPK3 to inhibit necroptosis ( Orning and Lien, 2021 ). Moreover, membrane cholesterol is essential for the activation and recruitment of caspase-8 and its non-apoptotic functions in cancer cells ( Kumar et al, 2018 ). Until now, there is no related study about the role of CASP8 in HNSCC, and our analysis can provide useful information for the in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, disruption of lipid raft microdomains has been foreseen as a rational therapeutic strategy in cancer treatment, more so for ER+ BCs that contain high amounts of cholesterol. Accumulating evidence has shown that the depletion of cholesterol from lipid rafts augments apoptosis thereby reducing carcinogenesis . Moreover, lipid raft disruption induces chemosensitivity as well as increases sensitivity to certain drugs such as tamoxifen .…”
Section: The Way Forwardmentioning
confidence: 99%